2008
DOI: 10.1007/s10529-008-9668-7
|View full text |Cite
|
Sign up to set email alerts
|

Enantioconvergent bioconversion of p-chlorostyrene oxide to (R)-p-chlorophenyl-1,2-ethandiol by the bacterial epoxide hydrolase of Caulobacter crescentus

Abstract: The enantioselective hydrolysis of eight racemic styrene oxide derivatives has been investigated by using the recombinant cell containing epoxide hydrolase (EH) of Caulobacter crescentus. Some styrene oxide derivatives were hydrolyzed via enantioconvergent manner so that enantiopure diol products could be prepared with a 100% theoretical yield. The recombinant cell containing C. crescentus EH exhibited an ability to hydrolyze racemic p-chlorostyrene oxide the most enantioconvergently, thus affording the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…There is no doubt that chiral pure epoxides and vicinal diols have an important role in the synthesis of pharmaceuticals, pesticides and cosmetics (Hwang et al 2008;Kotik et al 2005;Xu et al 2006). Glycidyl phenyl ether is a vital drug intermediate for the preparing aryloxy propanolamines (Bala et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that chiral pure epoxides and vicinal diols have an important role in the synthesis of pharmaceuticals, pesticides and cosmetics (Hwang et al 2008;Kotik et al 2005;Xu et al 2006). Glycidyl phenyl ether is a vital drug intermediate for the preparing aryloxy propanolamines (Bala et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar manner, the enantioconvergent biohydrolysis of styrene oxide 1 using the bacterial epoxide hydrolase from C. crescentus 47 provides the corresponding diol in 90% ee.…”
Section: Enantioconvergencementioning
confidence: 96%
“…Based on the above approach, the regioselectivity coefficient of CCEH, ANEH, and RGEH toward racemic styrene oxide was determined. Previously, recombinant CCEH was shown to attack predominantly (S)-styrene oxide at α carbon atom [14]. On the contrary, it was shown that recombinant ANEH and RGEH preferentially hydrolyzed (R)-styrene oxide predominantly into (R)-1,2-phenylethandiol with the retention of configuration (Table 1).…”
Section: Characterization Of Enantioselectivity and Regioselectivity mentioning
confidence: 96%
“…A novel marine fish EH gene from Mugil cephalus has been also cloned and characterized [12]. Recently, we have explored the enantioconvergent hydrolysis of racemic styrene oxide based on the enantio-flexibility of the C. crescentus EH (CCEH) and M. cephalus EH (MCEH) [13,14]. However, the MCEH could not be used in a preparative-scale biotransformation because of their low availability.…”
Section: Introductionmentioning
confidence: 99%